Prognostic Value of Serum Neurofilament Light Chain for Disease Activity and Worsening in Patients With Relapsing Multiple Sclerosis: Results From the Phase 3 ASCLEPIOS I and II Trials - Ziemssen, Tjalf; Arnold, Douglas L.; Alvarez, Enrique; Cross, Anne H.; Willi, Roman; Li, Bingbing; Kukkaro, Petra; Kropshofer, Harald; Ramanathan, Krishnan; Merschhemke, Martin; Kieseier, Bernd; Su, Wendy; et al. (Frontiers in Immunology, 2022)
Objective: To confirm the prognostic value of baseline serum neurofilament light chain (sNfL) for on-study disease activity and worsening in patients with relapsing MS (RMS). Background: Previous post-hoc studies suggested that sNfL could be a prognostic biomarker in RMS. In the phase 3 ASCLEPIOS I/II trials in which ofatumumab demonstrated better efficacy outcomes than teriflunomide, treatment with ofatumumab also led to significantly reduced sNfL levels compared to teriflunomide treatment. Design/methods: In this study, we report protocol-planned analyses from the pooled ASCLEPIOS I/II trials (N=1882). Per-protocol, patients were stratified by median baseline sNfL levels (9.3 pg/mL) into high (>median) and low (≤median) categories to prognosticate: annualized rate of new/enlarging T2 (neT2) lesions in year 1 and 2, annualized relapse rate, annual percentage change in whole brain (WB) and regional brain volume (thalamus, white matter [WM], cortical grey matter [cGM]) and disability outcomes. Similar analyses were performed for the recently diagnosed (within 3 years), treatment-naïve patients (no prior disease-modifying therapy) subgroup. Results: High versus low sNfL at baseline was prognostic of increased on-study T2 lesion formation at year 1 (relative increase: ofatumumab +158%; teriflunomide +69%, both p<0.001), which persisted in year 2 (+65%, p=0.124; +46%, p=0.003); of higher annual percentage change of WB volume (ofatumumab −0.32% vs −0.24%, p=0.044 and teriflunomide −0.43% vs −0.29%, p=0.002), thalamic volume (−0.58% vs −0.31%, p=0.047 and −0.94% vs −0.49%, p<0.001) and WM volume (−0.30% vs −0.19%, p=0.083 and −0.38% vs −0.18%, p=0.003) but not of cGM volume (−0.39% vs −0.32%, p=0.337 and −0.49% vs −0.46%, p=0.563). A single sNfL assessment at baseline was not prognostic for on-study relapses or disability worsening. Results were similar in the subgroup of recently diagnosed, treatment-naïve patients. Conclusion: This study confirms that baseline sNfL levels are prognostic of future on-study lesion formation as well as whole brain and regional atrophy in all RMS patients, including recently diagnosed, treatment-naïve patients.